Pendekatan Holistik Penatalaksanaan Tinea Pedis pada Ibu Rumah Tangga Usia 62 Tahun di Wilayah Kerja Puskesmas Sukarame - Febrina Aulia Natasya; Nasution, Syahrul Hamidi (Medula, 2024)
Dermatophytosis is a superficial infection caused by dermatophyte fungi. This infection is also often called tinea. Classification is based on the affected body part, namely tinea capitis (head), tinea faciei (face), tinea barbae (beard), tinea corporis (body), tinea manuum (hands), tinea cruris (groin), tinea pedis (feet), tinea unguinum (nails). The prevalence of dermatophytosis in Asia is 35.6%, while in Indonesia it is 52%. The risk factors are related to the agent, host, and environment. These factors include immunocompromised, high humidity, high temperature, increased urbanization, variations in fungal virulence. The purpose is application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient problem-solving framework using a patient-centered and family approach. This study is a case report. The data obtained are primary data obtained through autoanamnesis, alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical record. The results of this study are, patient Mrs. I 62 years old came with complaints of itching and redness in the foot area since two week before coming to the puskesmas. Complaints of itching worsen if the patient feet are damp. Physical examination revealed a numular sized eritematous lesion, the edges of the lesion had fine scales. Clinically the patient was diagnosed with Tinea pedis (ICD-10 B35.3). Furthermore, management, intervention and evaluation are carried out. In conclusion, holistic management can increase knowledge and change attitudes and behavior of patients, especially in patients wuth dermatophytosis. The role and support of the family is needed in the care and treatment of patients.